DNA methylation profiles for breast cancer subtype classifications: A translational study from microarray to methylation-specific PCR (MSP) - Panigoro, Sonar S.; Paramita, Rafika I.; Wanandi, Septelia I.; Fadilah, Fadilah; Wibisana, I GNG.; Sutandyo, Noorwati (Narra J, 2025)
Breast cancer subtypes can be categorized based on their gene expression profiles using immunohistochemistry into Luminal A, Luminal B, human epidermal growth factor receptor 2-positive (HER2+), and triple-negative breast cancer (TNBC) subtypes. However, immunohistochemistry has certain limitations that can lead to misclassification. DNA methylation is an epigenetic modification, and changes in the promoter region can alter gene expression and the quantity of functional protein synthesized, disrupting gene function. The aim of this study was to identify DNA methylation biomarkers for subtype classification in breast cancer using microarray and methylation-specific polymerase chain reaction (MSP) methods. DNA samples were extracted, subjected to bisulfite conversion and then used for both the microarray and MSP methods. This study successfully identified differentially methylated CpGs (DMCs) as biomarker for each subtype classification of breast cancer: Luminal A (hypermethylation of ADAMTSL2 gene; cg14397888), Luminal B (hypomethylation of ADAMTSL2 gene; cg14397888), HER2+ (hypermethylation of PTPRN2 gene; cg25910261), and TNBC (hypomethylation of LCLAT1 gene; cg15652532). The DMC biomarker found for the HER2+ subtype, hypermethylation in the PTPRN2 gene (cg25910261), has the potential to be used by healthcare providers to identify HER2+ patients and provide the HER2-targeted therapy to improve the patient’s survival. In addition, our developed MSP method could produce an effective diagnostic tool for classifying the Luminal A and Luminal B subtypes, with accuracies of 75% and 76%, respectively.